Expressão musical e musicalização através de práticas percussivas coletivas na Universidade Federal do Ceará. - Schrader, Erwwin (2011)
The present study aims at narrating the development trajectory of collective percussion music practices understood as an artistic movement and as musical education at the Federal University of Ceará (UFC), seeking knowledge, musical expressions as well as teaching and learning strategies of groups and individuals involved with percussion music. It also seeks to understand the process of building these practices in an academic environment in order to identify how they occur in the training of music teachers in an undergraduate course. The concepts of experiência significativa by Jorge Larrosa (2001) and autobiografia/biografia by Mikhail Bakhtin (2010) provided support to the construction of the thesis. In the course of the study some biographies of actor-subjects from the percussion music field were prepared and inserted in the text. At the same time, some devices of the action research supported the investigation which begins with a survey on the inclusion of percussion music practices in Brazilian universities followed by a study on the development of percussion music in artistic activities of popular culture at the Federal University of Ceará (UFC) academic setting, describing the trajectories of some traditional groups like: grupo Tradições Cearenses and grupo Brincantes Cordão do Caroá. The research paper also discusses about the constitution of the Center for Percussion Music of UFC (Núcleo de Música Percussiva da UFC) on Mestre Descartes Gadelha’s musical-rhythmic activities, highlighting some aspects of his education, artistic production and his contact with UFC. This work also presents theoretical and practical activities of the following subjects: Percussion Workshop I and Drum Workshop II, seeking to highlight their contribution to the training of music teachers. The knowledge and information about a collective percussion music culture are important dimensions of this study which are transformed into concrete ideas for a percussion-based experience in school and academic spaces.